Public Service Interpreting in Greece: Professionalization Challenges and Candidate Profiles for the National Interpreter Registry - Ioannidis, Anastasios (Estudios de Traducción, 2026)
In response to the growing demand for professional interpreters, the Greek Ministry of Migration and Asylum, in collaboration with the Ionian University’s Department of Foreign Language, Translation, and Interpreting, launched an initiative to establish a national registry of accredited public service interpreters. This paper examines the challenges of professionalizing the field by drawing on insights from two questionnaire-based surveys conducted as part of the project: one assessing interpreter-mediated interactions from the perspective of asylum officers and another analyzing the profiles of candidates who participated in the registry’s entry-level exams.The first survey, which collected responses from 16 public officers at the Greek Asylum Service, revealed persistent issues, including reliance on untrained interpreters, frequent breaches of ethical standards, inconsistencies in professional conduct, and a lack of trust between stakeholders. The second survey examined the profiles of 61 interpreter candidates, highlighting their diverse linguistic backgrounds, varying levels of Greek proficiency, and limited formal training in interpreting. Despite previous work experience, many candidates failed the entry exams. By correlating the findings from both surveys, this paper identifies systemic gaps in the professionalization of public service interpreting in Greece and underscores the urgent need for targeted reforms.